Biofeedback Exercise and its Relation to Pelvic Floor Muscle Strength: an Experiment at 3 Weeks and 6 Weeks Postpartum - Eighty Mardiyan Kurniawati, Eighty
Abstract Pelvic floor muscle weakness is closely related to the quality of life in women because this disorder can be caused by pregnancy and childbirth. Previous research has shown that pelvic muscle training can improve pelvic muscle health. This study aims to compare the strength of the pelvic floor muscles given biofeedback training at 3 weeks and 6 weeks postpartum. An experimental study was conducted on women who had vaginal delivery for the first time. The study was conducted at the post-partum clinic, a tertiary referral hospital in East Java, indonesia. This study involved 40 people randomly with 20 people in each treatment. The women were given pelvic floor exercises with the biofeedback method starting at 3 weeks post vaginal delivery and at 6 weeks post vaginal delivery. Exercises in this study used the biofeedback method for 4 weeks in both groups. Pelvic floor muscle strength in this study was measured by Myomed 932 pressure biofeedback in units of hPa. Data were analyzed statistically. There was no significant difference (p> 0.05) between the two groups, both maximal contraction (p = 0.283) and delta (p = 0.428) before undergoing exercise. The pelvic floor muscle group started at the third week showed increased muscle strength after biofeedback after 4 weeks (p <0.05). The pelvic floor group, starting the sixth week, showed improved pelvic floor muscle strength after 4 weeks of biofeedback training (p <0.05). The mean change in maximum contraction strength in the third week exercise group compared to 6 weeks of exercise after the second 4 weeks of biofeedback training was not significant (p = 0.881). Likewise, the mean change in pelvic floor muscle delta in both groups at the end of the evaluation was not statistically significant (p = 0.939). Pelvic floor muscle strength in primiparous post-biofeedback exercise started at 3 weeks postpartum is as good as exercise started at 6 weeks postpartum.